Gestión Administrativa en la Cooperativa de Ahorro y Crédito Occidental en el Cantón La Maná - Morales Yaguana, Bristhan del Rosario (2016)
The research on the design of a model of administrative management for Cooperativa de Ahorro y Crédito Occidental Cantón La Maná, allowed to extend efficient administrative processes, in order to provide excellent financial services to the customers and strengthen the growth institutional; this management model solved problems such as, the objectives which are not related to institutional vision, poor management of the computer system by the collaborators continuous, unrest in members due to the delay in the processes; to solve these disadvantages, the applied method was non-experimental research, besides this is required the application of instruments such as the interview, survey and statistical procedures for research; the results obtained by applying this process were guidelines to properly correct the flaws existed within the company , strategic planning, among others. As a main contribution to the aforementioned problems It was necessary the development of a administrative management model for mitigation and the respective changes that help the institution to provide a quality and efficient service.We conclude stating that the proposed model will serve the cooperativa as a support tool for the most relevant decisions that will help to improve the administration of the cooperativa always looking for the institutional growth, better positioning in the financial market and the satisfaction of customers. It should be noted that proper administrative management allows to reach those goals that were raised at the beginning of operations and facilitates the accomplishment of the tasks systematically.